THE PREVENIENCE AND PHENOMENALITY OF GRACE, OR, THE ANTERIORITY OF THE POSTERIOR - Purcell, Michael (Heythrop journal, 2009)
This article argues the possibility of a phenomenology of Grace on the basis of response. Its key phenomenological interlocutor is Emmanuel Levinas. The theology of grace might be said to be the fundamental theological doctrine, embracing as it does all other theologies, yet the theology of grace has been a focus of theological debate and dispute throughout history. This article suggests that Levinas' ethical metaphysics, when applied to theology, gives theology a new phenomenological voice in which the theology of grace might be articulated. It begins by arguing the significance of the ordinary and the everyday and the sincerity of intentional life in the world, and then proceeds to develop the notion of the prevenience of grace (gratia praeveniens) in terms of Levinas notion of the posteriority of the anterior/anteriority of the posterior. Grace is known in its effects.